Onicocriptosis recidivante: tratamiento postoperatorio con homeopatía - Benito Aguilar, Luis De (Revista Internacional de Ciencias Podológicas, 2007)
The clinical case that it is exposed next is a recidivante and refractory Onicocriptosis to other treatments with which it was decided to make conventional surgical matricectomia by means of the technique of Winograd. We used as postoperating medication of election a served and administered homeopatico grain medicine in this case by oral route called Arnica Montana whose objective consists of diminishing the pain and the postoperating inflammation
Keywords: Homeopatia; Onicocriptosis; Technique of Winograd